2020
DOI: 10.1016/j.cmet.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Patch-Seq Links Single-Cell Transcriptomes to Human Islet Dysfunction in Diabetes

Abstract: Pancreas patch-seq provides a single-cell survey of function-transcriptome pairing in 1,369 islet cells from donors with and without diabetes • Expression of a specific subset of genes predicts b-cell electrophysiology in transcriptomefunction networks.• Compromised b-cell function in T2D correlates with altered ETV1 expression and inflammatory pathways• Functional heterogeneity in a-cells maps to ER stress and islet lineage markers• Application of patch-seq to cells from rare cryopreserved islets from donors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
254
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 202 publications
(289 citation statements)
references
References 90 publications
13
254
0
1
Order By: Relevance
“…HPAP (Kaestner et al, 2019), Baron et al (Baron et al, 2016), and Camunas-Soler et al (Camunas-Soler et al, 2020) datasets showed that less than 1% of acinar or ductal cells expressed ACE2, whereas ~35% of both cell types expressed TMPRSS2. In the dataset by Segerstolpe et al (Segerstolpe et al, 2016), ACE2 was expressed in ~20% of acinar and ductal cells, whereas TMPRSS2 was expressed in greater than 75% of both populations ( Figure 1B).…”
Section: Coate-6mentioning
confidence: 98%
See 4 more Smart Citations
“…HPAP (Kaestner et al, 2019), Baron et al (Baron et al, 2016), and Camunas-Soler et al (Camunas-Soler et al, 2020) datasets showed that less than 1% of acinar or ductal cells expressed ACE2, whereas ~35% of both cell types expressed TMPRSS2. In the dataset by Segerstolpe et al (Segerstolpe et al, 2016), ACE2 was expressed in ~20% of acinar and ductal cells, whereas TMPRSS2 was expressed in greater than 75% of both populations ( Figure 1B).…”
Section: Coate-6mentioning
confidence: 98%
“…Median expression level of ACE2 and TMPRSS2 mRNA was much less than transcripts of such key islet-enriched genes in human a and b cells (~84% and 92% lower than a and b cellenriched transcripts, respectively, for DNA-binding transcription factors) ( Figure 1A; n=7-8 adult donors per study). In addition, analysis of four single-cell (sc) RNA-seq datasets of human pancreatic islets (Baron et al, 2016;Camunas-Soler et al, 2020;Kaestner et al, 2019;Segerstolpe et al, 2016) revealed that ACE2 and TMPRSS2 transcripts were either undetectable or minimally expressed in all endocrine subsets ( Figure 1B and S3J). We note that this includes analysis of the robust Human Pancreas Analysis Program (HPAP) dataset that includes more than 25,000 cells (Kaestner et al, 2019) from 11 normal donors and is confirmed by the analysis of three previously reported, but smaller, datasets ( Figure 1B and S3J).…”
Section: Coate-5mentioning
confidence: 99%
See 3 more Smart Citations